The Urgency of Ammending Jinayat Qanun in Eradicating Cyber Sexual Crime in Aceh, Indonesia - Abdul Jalil Salam; Mursyid Djawas; Abidin Nurdin; Delfi Suganda; Dedy Sumardi (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
As a special province in Indonesia with the jurisdiction to enforce Islamic law, Aceh has enacted Jinayat Qanun to regulate criminal actions. However, incidents of sexual offenses in cyberspace remain unregulated. This article seeks to elucidate the necessity for amendments to the Jinayat Qanun, particularly for instances of sexual offenses in cyberspace. It employs empirical research methodologies assessed via a legislative framework utilizing system theory. Data was gathered through meticulous literature review and extensive interviews. This study reveals that online prostitution has emerged as a global concern, reflecting the adverse effects of contemporary advancements. In Aceh, the currently enacted Jinayat Qanun is perceived as necessitating ammandments. These modifications are tailored to the evolving conditions of society. According to system theory, Jinayat Qanun substantially addresses the issue of online prostitution implicitly. However, obstacles persist within the legal framework and cultural context. Indonesia's legal structure and cultural dynamics, particularly in Aceh, pose significant challenges, underscoring the need for collaboration among various stakeholders, including judges, prosecutors, law enforcement, ulama, and community leaders.